2014
DOI: 10.2174/1874325001408010052
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Acute Distal Biceps Tendon Ruptures Using Mitek Anchors: A Retrospective Study

Abstract: Purpose of this Study:The aim of this study was to evaluate the outcomes of surgical intra-osseous fixation of the distal tendon of the ruptured biceps brachii muscle using Mitek anchors.Materials and Methods:Between 2005 and 2011, seven patients underwent unilateral distal biceps tendon repair using Mitek anchors. All patients were men aged between 36 and 47 years. Six patients were assessed by physical examination and use of the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire.Results:Surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Our present study shows that clinical outcomes are comparable to those reported previously in the literature 1,7,9,17,19,24 (see Table 2). All patients regained full elbow range of motion at an average of 5.4 months and demonstrated satisfactory functionality with an average QuickDASH score of 6.5.…”
Section: Discussionsupporting
confidence: 91%
“…Our present study shows that clinical outcomes are comparable to those reported previously in the literature 1,7,9,17,19,24 (see Table 2). All patients regained full elbow range of motion at an average of 5.4 months and demonstrated satisfactory functionality with an average QuickDASH score of 6.5.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have been conducted regarding the best treatment of distal biceps tendon rupture, such as the use of one or two incisions, 4 anatomic or nonanatomic restoration of the ruptured tendon, and the kind of materials that should be used. 11,[13][14][15][16] Research is focused on measuring parameters in cadavers, usually the load to failure. Our study was conducted in humans, making it impossible to measure the load to failure.…”
Section: Resultsmentioning
confidence: 99%
“…While in some studies Endobutton-type devices seem to provide stronger initial repair, 10 suture anchor techniques-in most studies-present inferior biomechanical properties. 13,14 On the other hand, interference screws alone seem to be weaker than other techniques but, apparently, they recreate native load and stiffness. 15,17 More recently, the use of hybrid fixation, such as the fixation with both a button-type device and an interference screw, has given some promising results regarding the initial fixation strength and the gap formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(E) Lateral and AP Xray views of the right forearm and 2 biceps anchors with distal anchor appearing to protrude through posterior aspect of radius (arrow head). (F) Schematic depiction of biceps tendon anchors, with anchor morphology shown in the top right corner [4] . …”
mentioning
confidence: 99%